Daily fluctuations in occupation with and worry about COVID-19. (November 2021) - Lodder, G.M.A.; Van Halem, S.; Bülow, A.; van Scheppingen, M.A.; Weller, J.; Reitz, A.K.
Abstract: In the first week after the first COVID-19 patient was reported in the Netherlands, we conducted a pre-registered momentary assessment study (7 surveys per day, 50 participants, 7 days) to study the dynamic relationship between individuals' occupation with and worries about COVID-19 in daily life, and the moderating role of neuroticism in this relationship. At the group level, higher scores on occupation and worry co-occurred, and occupation predicted worry 1 h later, but not vice versa. There were substantial individual differences in the magnitudes and directions of the effects. For instance, occupation with COVID-19 was related to increases in worry for some but decreases in worry for others. Neuroticism did not predict any of these individual differences in the links between worry and occupation. This study suggests that it is important to go beyond group-level analyses and to account for individual differences in responses to COVID-19. Highlights: Individuals differ substantially in size and direction of the relationship between worry about and occupation with COVID-19 Neuroticism was not significantly related to individual differences in these relationships Advice to limit news-intake surrounding COVID-19 when worried may thus not be applicable to everyone